Prevalence of falls and comparison of health-related physical fitness factors between different faller categories among institutionalized older adults in Kandy District of Sri Lanka. - Welgama Ihalage Suheja Madhushani Ihalage; Vidhana Ralalage Chalana Sithara Wijebandara; Diwalawaththe Gedara Wathsala Sewwandi Wickramakumari; Wickramasingha Mudiyanselage Buddhini Dilesha Wickramasingha; Rathnayaka Mudiyanselage Ruwan Keerthi Sampath; Manchanayake Mudiyanselage Jinali Pabodha Manchanayake; Esther Liyanage (PLoS ONE, 2024)
Falls can be identified as one of the main issues in elderly population which can lead to serious consequences. Elderly population can be subdivided as community dwelling older adults and institutionalized older adults. The components of health-related physical fitness factors play an important role in the perspective of healthy ageing. The objective of the study was to determine the prevalence of falls and to compare health-related physical fitness factors between different fall categories among institutionalized older adults. This descriptive cross-sectional study comprised of one hundred and seventy-two elders above 60 years of age, living in registered elder's homes in Kandy District. The prevalence of falls was determined by the number of falls reported by the subjects. They were further categorized as non-fallers, fallers, and frequent fallers depending on the number of falls. Body Mass Index (BMI) for body composition, 2-minute walk test for cardiovascular endurance, 30 second sit to stand test for muscle strength and endurance, hand grip strength for upper body strength, chair sit and reach test for lower body flexibility and back scratch test for upper body flexibility were the measures used to assess health-related physical fitness factors. The prevalence of falls is presented as percentage and the health-related factors were compared between the three faller categories using one-way ANOVA and pairwise comparison was performed using Scheffe test. The prevalence of falls was 47.1%. There was a significant difference in BMI, cardiovascular endurance, and lower body flexibility between the three categories of fallers. Higher BMI, lower cardiovascular endurance and lower flexibility in the lower body were associated with increased prevalence of falls (p<0.05). There was no significant difference in body fat percentage, hand grip strength, lower body muscle strength and endurance and upper body flexibility (p>0.05). The findings suggest that, BMI, cardiovascular endurance, and lower body flexibility must be addressed and managed, while designing intervention programs for falls prevention among institutionalized older adults.